Nutritional strategies to alleviate heat stress effects through feed restrictions and feed additives (vitamins and minerals) in broilers under summer conditions - Mohamed, Abdelhameed Salah Abdelhameed (2019)
This experiment was aimed to determine the best strategies for alleviating the detrimental effects of heat stress by feed restriction (FR) in hot times and dietary supplementation with Vit.+Min. (vitamins and minerals) by their impacts on growth parameters, mortality rate, serum biochemistry indices and carcass traits of broiler under summer conditions in the open-sided house. A total of 420 broilers of Ross 308 (unsexed 7-day-old) were equally divided into 7 treatments (T). Throughout the experiment, chicks in T1 (control) fed ad libitum on basal diets, FR was applied in T2, T3 and T4 as followed 2, 3, 4 hours (h) without feeding respectively. Supplemental vitamin C (Vit.C) + vitamin E (Vit.E) + chromium (Cr) + zinc (Zn) as followed 100+100+0.5+50 (T5), 150+150+1.0+75 (T6), 200+200+1.5+100 (T7) mg/kg diet respectively. It was found that FR and feed additives improved body weight, weight gain, and significantly decreased feed conversion, mortality rate, and abdominal fat of stressed broiler. Applying FR (3, 4 h) and supplementation with Vit.+Min. (T6, T7) significantly increased total serum protein and statically decreased total serum cholesterol. Overall results conducted that FR for 3 h (T3) and dietary supplementation (T7) have the most significant results which indicate the vital role of FR and supplementation with Vit.+Min. in stressed broilers.